Implementasi Metode Rank Order Centroid Dan Multi Attributive Border Approximation Area Comparison Dalam Penerimaan Karyawan - Muhamad Hidayatullah; Ali Ikhwan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The presence of employees is an important aspect of a company. Therefore, the employee recruitment process must be carried out professionally and carefully to ensure that the selected employees can make a meaningful contribution to the company. If the recruitment process is carried out subjectively and conventionally, the company may face difficulties in making the right decisions regarding employee recruitment. If this continues over a long period of time, it can have a negative impact on company performance and hinder the achievement of goals. To obtain prospective employees who are competent and in accordance with the required classification, employee recruitment requires appropriate selection. The aim of this research is to build a decision support system in employee recruitment so that it can help companies in determining the right employee candidates. To ensure objectivity in the employee recruitment process, it is necessary to use appropriate and appropriate methods in employee recruitment. The methods used in this research are Rank Order Centroid (ROC) and Multi-Attributive Border Approximation Area Comparison (MABAC). In the employee recruitment process, four criteria are used, namely honesty, presence, attitude and skills. The results of the decision support system using the ROC and MABAC methods are getting a ranking of prospective employees so that they become the best recommendations in the employee recruitment process